The Role of Teachers in Enhancing Quranic Reading Skills Using the Tartil Method - Saini, Mukhamat; Nurvaniati, Ikke Aprilia; Sunoko, Ahmad; Choirudin, Moch; Ramdhani, Fajri Zulia (STAI Miftahul Ula Nganjuk, 2024)
This study investigates the role of teachers in enhancing Quranic reading skills among sixth-grade students at Madrasah Ibtidaiyah Nurussalam, focusing on their roles as motivators and evaluators. Using a qualitative field approach, data were collected through observation, interviews, and documentation. The research aims to understand how teachers contribute to improving students' Quranic reading skills, while examining their influence as motivators and evaluators. The findings indicate that teachers play a vital role in guiding students towards achieving the set goals for Quranic reading. As motivators, teachers encourage students by offering rewards or points for each achievement, creating a positive learning atmosphere that promotes continuous improvement. These incentives enhance students' enthusiasm and engagement in learning. In addition to motivating students, teachers also serve as evaluators. They assess students’ Quranic reading abilities through regular evaluations, which help determine the effectiveness of teaching methods and students’ progress. This evaluative role is essential in identifying areas where students need further assistance and adjusting teaching strategies accordingly. Evaluations also provide teachers with insights into the students' learning outcomes, enabling them to refine their approach. Furthermore, the evaluation process allows teachers to prepare comprehensive reports on students' progress, which are shared with parents and school administrators. These reports play an important role in ensuring students receive the necessary support. Overall, the study highlights the critical role of teachers as both motivators and evaluators in improving Quranic reading skills and fostering effective learning at Madrasah Ibtidaiyah Nurussalam